Establishment of inherent stability of pramipexole and development of validated stability indicating LCâUV and LCâMS method - Shubhangi M. Pawar; Laxman D. Khatal; Satish Y. Gabhe; Sunil R. Dhaneshwar (Elsevier, 2013)
Pramipexole belongs to a class of nonergot dopamine agonist recently approved for the treatment of early and advanced Parkinson's disease. A validated specific stability indicating reversed-phase liquid chromatographic method has been developed for the quantitative determination of pramipexole in bulk as well as in pharmaceutical dosage forms in the presence of degradation products. Forced degradation studies were performed by exposition of drug to hydrolytic (acidic and basic), oxidative and photolytic stress conditions, as defined under ICH guideline Q1A (R2). Significant degradation was observed under hydrolytic, oxidative and photolytic conditions and the degradation products formed were identified by LCâMS. Keywords: Degradation products, Forced degradation/stress studies, Liquid chromatography mass spectrometry, Pramipexole, Reversed-phase liquid chromatography